Sunflower wax recovered from oil tank settlings: Revaluation of a waste product from the oilseed industry - Redondas, Cintia Elizabeth (2019)
BACKGROUND: The sunflower oil industry produces a large amount of waste that is not currently commercially exploited, as in the case of oil‐tank settlings. The recovery of a high value‐added by‐product, such as sunflower wax, would increase the commercial value of this waste. In this original research paper, a method that allows the recovery and purification of this by‐product was developed. The wax was characterized and its potential use as an organogelator agent was investigated. RESULTS: The waste sample was composed of 45.1% oily material, 16.9% of this being impure waxes. Purification was performed through two different methods, obtaining three waxes with different degrees of purity. All the waxes were composed of wax esters with a range of 40–60 carbon atoms, exhibiting traces of carotenes, free fatty acids, and free fatty alcohols. The presence of phospholipids was observed in two of them. The third wax presented a higher total wax ester content and physicochemical characteristics (color and thermal behavior) similar to those of commercial sunflower waxes, and was the most efficient organogelator agent, requiring only a small amount of wax (1.5%) to structure high oleic sunflower oil. CONCLUSION: It was verified that sunflower wax could be recovered from oil‐tank settlings. A purification method that allowed sunflower wax with similar physicochemical properties to those of commercial waxes to be obtained was also developed. The purified waxes were capable of structuring high oleic sunflower oil. © 2019 Society of Chemical Industry